Aplicacion del control integrado del acaro rojo Panonychus ulmi (Koch) en parcelas comerciales de manzano - Costa-Comelles, J.=700 1 Santamaria, A.; Garcia-Mari, F.; Laborda, R.; Soto, A.
(En, Es)
ilus., 8 ref.
Keywords: PANONYICHUS ULMI; MANZANA; LUCHA INTEGRADA; ESPAÑA